SISTEM PEMBELAJARAN BOARDING SCHOOL DALAM PENGEMBANGAN ASPEK KOGNITIF, PSIKOMOTORIK, DAN AFEKTIFSISWA MAN INSAN CENDEKIA BENGKULU TENGAH - Surya Atmaja (UIN Fatmawati Sukarno Bengkulu, 2019)
The purpose of this study was to analyze the boarding school learning system in the development of cognitive, psychomotor and affective aspects of students of Central Bengkulu Scholar Individuals. This research is motivated by the problem of the difficulty of developing students’ psychomotor and affective domains due to time constraints. This research is a qualitative research whose data collection techniques consist of observation, interview and document analysis. The results of the study showed that the application of the boarding school learning system in the Central Bengkulu Scholar Individual MAN consisted of two learning models namely morning learning and night learning. Learning in the morning with the Fuly system and learning at night is learning the pesantren which starts at the evening prayer until 8:00 p.m. As for all activities that exist in the Middle Bengkulu Scholar Human Institute MAN are basically inseparable from the development of cognitive, psychomotor, and affective aspects of students. Then there are also some strengths, weaknesses, opportunities and challenges in the boarding school learning system in its development towards cognitive, psychomotor, and affective aspects of students of Central Bengkulu Scholar Individuals.